Clinical and molecular characteristics of forty Chinese children with essential thrombocythemia: A single‐center, retrospective analysis. (25th January 2023) - Zhang, Luyang; Chen, Xiaoli; Hu, Tianyuan; Xu, Zefeng; Yang, Wenyu; Fu, Rongfeng; Zhang, Lei; Zhu, Xiaofan
Summary: Due to the infrequency of essential thrombocythemia (ET) in children, little is known about its pathophysiological mechanism. To learn about the clinical and molecular features of Chinese children with ET, we retrospectively analysed 40 children with ET in a single center from 2015–2021. More than half of the children (51.3%, 20/39) were asymptomatic at diagnosis. Nearly half of the children (48.7%, 19/39) had microvascular symptoms, including headache, dizziness, stomachache, and paresthesia. Only two cases experienced vascular events. The proportion of children with typical "driver gene mutations" (i.e., JAK2 p.V617F, CALR exon 9, or MPL exon 10 mutation) was low (12.5%, 5/40). The equivalent ratio of children carried atypical driver gene mutations; however, 30 (75%) patients did not harbour driver gene mutations. Children carrying JAK2 p.V617F had lower platelet count (938 × 10 9 /L vs. 1654 × 10 9 /L, p  = 0.031) compared to those without driver gene mutations. Cases harbouring typical driver mutations had higher median WBC counts than those without driver gene mutations (15.14 × 10 9 /L vs. 8.01 × 10 9 /L, p  = 0.015). Compared to those without driver gene mutations, cases carrying typical and atypical driver gene mutations were both younger (median ages were 12, 6, and 7 years old, respectively; p  = 0.023). The most prevalent non‐driver gene mutations and those mutations with prognostic significance in adult counterparts were less common in children with ET compared to adults with ET.